Periodontal preparation for orthodontic treatment – a literature review - Szepietowska, Zofia; Majdanik, Wioleta; Górska, Renata; Zadurska, Małgorzata; Plakwicz, Paweł (Forum Ortodontyczne / Orthodontic Forum, 2019)
Orthodontic treatment of patients with periodontal problems constitutes an important issue in everyday orthodontic practice. The most frequent problems include periodontal inflammatory diseases and mucogingival defects, mainly recessions. Orthodontic movements in the range of healthy supporting tissues and mucosa are key for optimal clinical effects. Hence, eliminating inflammation and obtaining correct parameters of the muco-gingival complex is required. Aim. The aim was to analyse literature on orthodontic treatment of adult patients with selected periodontal problems. Material and methods. Publications on periodontology, found in PubMed database 2and other repositories, were searched. Articles on orthodontic treatment of patients with periodontal problems were selected and analysed. This publication is based on research results published in 40 works in the period 2002-2018. Results. Periodontal diagnosis is important in planning orthodontic treatment. The main factor is the dental plaque, which is responsible for the development of periodontitis. Periodontal treatment begins with eliminating an inflammatory condition by non surgical methods. Periodontal surgery is common too, as it also serves to correct defects caused by periodontitis. Another important group of defects is that of muco-gingival origin, which requires an early diagnosis and consideration in planning orthodontic movements. Most defects must be corrected prior to orthodontic therapy. Discussion. Detection of problems in periodontal structures or the muco-gingival area ought to precede orthodontic treatment. This enables early periodontal intervention and the planning of orthodontic treatment, with consideration of the resistance of supporting tissues and various conditions of the muco-gingival complex. Conclusions. Close cooperation between orthodontist and periodontologist provides safe and predictable orthodontic treatment of patients with periodontal problems. (Szepietowska Z, Majdanik W, Górska R, Zadurska M, Plakwicz P. Periodontal preparation for orthodontic treatment - a literature review. Orthod Forum 2019; 15: 39-49).